Challenges in the quality of herbal medicinal products with a specific focus on contaminants. Issue 2 (11th August 2019) - Steinhoff, Barbara
Abstract: Background: The complex regulatory framework for the quality of herbal medicinal products, in particular with regard to potential contaminants, consists of legal provisions including Pharmacopoeia requirements, relating to limits as well as in most cases to methods for determination. Objective: This review intends to provide an overview on the legal requirements for testing potential contaminants in herbal drugs used for the production of herbal medicinal products. Methodology: The following issues are described and discussed: For the assessment of pesticide residues, Chapter 2.8.13 of the European Pharmacopoeia and Regulation (EC) 396/2005 applies, for heavy metals the general Pharmacopoeia monograph as well as the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) Q3D guideline on elemental impurities. The Pharmacopoeia also includes limits and acceptance criteria for microbiological purity and aflatoxins, respectively. Polycyclic aromatic hydrocarbons are mentioned in Regulation (EC) 1881/2006 for food as well as in a Reflection Paper on herbal medicinal products. For several years, a potential contamination with pyrrolizidine alkaloids was discussed which led to measures being imposed on industry and health authorities. Results: Various examples demonstrate that the evaluation of data from daily analytical practice is extremely useful to gain an overview on the occurrence of residues and/or contaminants in herbal drugs and herbal preparations. Such evaluations might assist manufacturers in their individual risk assessment and the definition of their testing strategies and contribute to guarantee the quality and safety of the marketed products. Conclusion: Annual data evaluations demonstrate that a remarkable decrease of the pyrrolizidine alkaloid content burden in herbal drugs and extracts used for the production of herbal medicinal products has been achieved over the past few years. However, it has also become clear that this issue cannot be completely solved in the near future. Abstract : This review summarizes the legal requirements for testing potential contaminants in herbal drugs used for the production of herbal medicinal products. Respective substances comprise e.g. pesticides, heavy metals, mycotoxins and pyrrolizidine alkaloids. Various examples of data evaluations from daily analytical practice are given which present an overview on the actual situation and might assist manufacturers in defining their testing strategies.